Less-Studied Technology-Critical Elements (Nb, Ta, Ga, In, Ge, Te) in the Marine Environment: Review on Their Concentrations in Water and Organisms - Romero-Freire, Ana; Santos-Echeandía, Juan; Neira, Patricia; Cobelo-García, Antonio (Frontiers in Marine Science, 2019)
The development in recent years of new technological and energy-related applications has increased the use and demand of a specific group of trace elements (Technology-Critical Elements, TCEs). Among the TCEs, there are a number of elements (Nb, Ta, Ga, In, Ge, Te) for which their biogeochemical cycles and their ecotoxicology and uptake by biota has been scarcely studied; they are known as Less-Studied TCEs (LSTCEs). Here we present a review on the concentrations of LSTCEs in marine waters and biota. We show that whereas oceanic profiles have been reported for all LSTCEs, and their geochemical behavior is well-constrained for some of them (e.g., Ga, In, Ge), only very few studies are available on the concentrations and behavior of these elements in estuarine and coastal waters which makes impossible the assessment of their status in environmentally impacted coastal areas. In marine biota, despite of the fact that concentrations have been reported in several organisms, information on the factors controlling the LSTCEs uptake or their potential to be biomagnified through the food web is mostly missing. It is therefore encouraged further research in order to have a better assessment on the impact of the uses of these metals on the concentrations of LSTCEs in such sensitive coastal zones, including their concentrations, bioavailability, thresholds for non-lethal endpoints and their capability of biomagnification.